Design and Rationale of the APELOT Trial: A Randomized, Open-Label, Multicenter, Phase IV Study to Evaluate the Antiplatelet Effect of Different Loading Dose of Ticagrelor in Patients With Non-ST Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention. Issue 22 (May 2016) - Liu, Hui-Liang; Wei, Yu-Jie; Jin, Zhi-Geng; Zhang, Jiao; Ding, Peng; Yang, Sheng-Li; Luo, Jian-Ping; Ma, Dong-Xing; Liu, Ying; Han, Wei
Abstract : Abstract: Ticagrelor is a direct acting on the P2Y12 receptor blocker, which provides faster and greater platelet inhibition than clopidogrel. However, several studies suggested that in ST-segment elevation myocardial infarction patients undergoing percutaneous coronary intervention (PCI), ticagrelor exhibits initial delay in the onset of antiplatelet action. Unlike ST-segment elevation myocardial infarction, in non-ST-segment elevation acute coronary syndrome (NSTE-ACS), management pathways are highly variable, and some patients may require surgery. Effect of higher loading dose (LD) of ticagrelor in patients with NSTE-ACS in providing faster and stronger inhibition of platelet aggregation is unknown and needs to be explored further. The AntiPlatelet Effect of different Loading dOse of Ticagrelor trial is an interventional, randomized, open-label, multicenter, phase IV trial designed to evaluate whether a high LD (360 mg) of ticagrelor compared with the conventional LD (180 mg) will result in a higher inhibition of platelet aggregation without increasing bleeding events in NSTE-ACS participants undergoing PCI. A total of 250 NSTE-ACS participants will be randomized to receive a ticagrelor LD (360 or 180 mg), followed by a maintenance dose of 90 mg twice a day (bid) starting 12 hours after the LD. The primary endpoint is platelet reactivity index measured by vasodilator-stimulated phosphoprotein phosphorylation 2 hours after the LD, and the secondary endpoints include occurrence of periprocedural myocardial infarction and bleeding events. The AntiPlatelet Effect of different Loading dOse of Ticagrelor trial will provide important information on the risks and benefits of a high LD (360 mg) of ticagrelor in achieving a faster and stronger platelet inhibition compared with the conventional LD (180 mg) in NSTE-ACS patients undergoing PCI.